Modified lithium borohydride solid electrolyte and preparation method thereof
By doping and compounding LiBH4 and B2O3 under an inert gas atmosphere, a high-performance lithium borohydride solid electrolyte is formed, which solves the problems of low room temperature conductivity and dendrite in traditional lithium borohydride electrolytes, and achieves high energy density and safety Solid-state lithium-ion battery applications.
Patent Information
- Application Number
- CN202411482155.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional lithium borohydride solid electrolyte has low ionic conductivity at room temperature and is easy to form dendrites, which limits its application in lithium-ion batteries. The existing modification methods have not yet fully improved their oxidative stability and electrochemistry. performance.
By mixing LiBH4 and LiX under an inert gas atmosphere, high-energy ball milling and heating treatment are carried out to form lithium halide-doped LiBH4, and then compound with B2O3 to form (xLiBH4-LiX)y-B2O3 solid electrolyte, improving its ionic conductivity and electricity Chemical stability.
It significantly improves the room temperature ionic conductivity, electrochemical stability and compatibility of lithium borohydride-based solid electrolyte, is suitable for large-scale production, and has a simple process and low cost.
Smart Images

Figure CN119297384A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of all-solid-state battery electrolyte preparation, and specifically relates to a modified lithium borohydride solid electrolyte and a preparation method thereof. Background Art
[0002] Rechargeable lithium-ion batteries (LIBs) have been widely used in portable electronic devices, electric vehicles, power grids, and energy storage. The electrolytes widely used in commercial LIBs are traditional organic liquid electrolytes, but their high flammability and uncontrollable dendrite growth may endanger the safety of the battery system. The evaporation or leakage of the electrolyte will not only lead to irreversible capacity decay of lithium-ion batteries, but also cause device damage after long-term use. The non-bending and non-flammable properties of solid electrolytes ensure that the battery can effectively avoid lithium dendrites while improving battery safety, so it is expected to solve these problems and promote the practical application of lithium-ion batteries.
[0003] Solid electrolytes have higher safety, thermal stability and a wider voltage window. They can match high-voltage positive electrodes and lithium metal negative electrodes to achieve higher energy density. Inorganic solid electrolytes can operate in a wide temperature range (-50 to 200 °C). Among them, lithium borohydride (LiBH4) is a very promising fast ion conductor. Lithium borohydride has the advantages of light weight, high mechanical toughness and stability to lithium, which is conducive to achieving the goal of high energy density and interface compatibility of lithium-ion batteries. However, the fast conduction of lithium ions in LiBH4 only occurs in the high-temperature hexagonal phase, and the ionic conductivity at room temperature (10 -8 S cm -1 ) is still difficult to meet the application standards, limiting the practical application of LiBH4 as a solid electrolyte.
[0004] In order to improve the ionic conductivity of room temperature LiBH4 solid electrolyte, a variety of modification methods have been explored: (1) anion and cation doping: by ion doping, the low-conductivity orthorhombic structure is changed to present a special crystal structure with high conductivity, thereby improving the mobility of lithium ions; (2) second phase recombination: by introducing a second phase to expand the lithium ion transmission channel, the lithium ion transmission path is changed, thereby reducing the activation energy of migration; (3) introduction of an inert second phase with low electronic conductivity: usually a high-conductivity interface layer is formed at the interface between the two phases or a new high-conductivity substance is generated, which is conducive to the rapid transmission of lithium ions. In addition, the actual application of LiBH4 is limited by dendrite growth and narrow potential window. Studies have shown that high electronic conductivity is the main reason for dendrite proliferation because it accelerates the oxidative decomposition of the electrolyte. Lithium dendrites grow preferentially through gaps and grain boundaries, which is also the main factor affecting lithium ion transmission. For example, patent CN 109244535A discloses a method for preparing a lithium borohydride-based solid electrolyte, wherein halogen-doped lithium borohydride is mixed with a mesoporous material in a certain proportion, and then heated and melt-impregnated in a high-pressure hydrogen atmosphere, and then cooled to obtain a nano-confined halogen-doped lithium borohydride-based solid electrolyte; the obtained solid electrolyte has good electrochemical stability, but the ionic conductivity needs to be improved. The electrochemical performance of lithium borohydride-based solid electrolytes modified by the current method is still far from commercial use. Therefore, which simple and efficient method is used to improve the oxidation stability, room temperature ionic conductivity and electronic conductivity of lithium borohydride-based solid electrolytes, thereby comprehensively improving their electrochemical performance, is a key issue in realizing the commercial application of lithium borohydride-based solid electrolytes. Summary of the invention
[0005] The present invention provides a modified lithium borohydride solid electrolyte and a preparation method thereof, which overcomes the defects of conventional lithium borohydride solid electrolytes. The prepared material has excellent ionic conductivity and electrochemical stability, improves electrode compatibility, and has a simple preparation process, good repeatability, and is suitable for large-scale production.
[0006] A method for preparing a modified lithium borohydride solid electrolyte comprises the following steps: (1) mixing LiBH4 and LiX in a certain ratio under an inert gas atmosphere to obtain a mixture; (2) High-energy ball milling of the mixture of LiBH4 and LiX under an inert gas atmosphere; (3) placing the product in an inert gas atmosphere and heating it to a predetermined temperature and then keeping it warm to obtain a xLiBH4-LiX (x = 1-5) electrolyte; (4) mixing xLiBH4-LiX electrolyte and B2O3 in a certain ratio under air-tight conditions (H2O < 0.01 ppm, O2 < 0.01 ppm) to obtain a mixture; Under an inert gas atmosphere, the mixture of xLiBH4-LiX and B2O3 was subjected to high-energy ball milling to obtain a doped and composite synergistically modified (xLiBH4-LiX)y-B2O3 (y=10~20) solid electrolyte.
[0007] In the above steps, the LiX in step (1) is one or more of LiCl, LiBr and LiI; The inert gas in steps (2) and (5) is argon, helium or nitrogen; the high-energy ball mill is a planetary ball mill with a ball-to-material ratio of (70-140):1, a ball mill revolution speed of 350-600 rpm, and a ball milling time of 1-5 hours; under a protective atmosphere, LiBH4 and oxide particles are mixed according to the formula and then subjected to high-energy ball milling, which has the characteristics of fast and high efficiency, so that the sample is evenly mixed to obtain a composite of lithium borohydride and boron oxide particles; the setting of the high-energy ball milling ball-to-material ratio directly affects the ball milling effect. If the ball-to-material ratio is too low, it may lead to poor ball milling effect; if the ball-to-material ratio is too high, the energy consumption is large. A reasonable ball-to-material ratio can give full play to the impact and friction of the ball. In step (3), the ball-milled product is heated in an inert gas atmosphere at a heating rate of 5°C / min to 110-150°C and kept warm for 1-5 h to allow LiBH4 and LiX to react fully, and then cooled to room temperature to obtain LiX-doped LiBH4 electrolyte. An appropriate reaction temperature should be selected. If the temperature is too low, the two cannot react completely; if the temperature is too high, raw material loss will result.
[0008] The modified lithium borohydride solid electrolyte prepared by the above method is a solid solution formed by lithium halide and LiBH4, thereby stabilizing LiBH4 in a state that is conducive to the conduction of lithium ions to the hexagonal phase, and then densifying the grain gaps through B2O3 composite, further reducing the grain boundary impedance and thereby improving the ionic conductivity.
[0009] Beneficial effects: The present invention provides a modified lithium borohydride solid electrolyte and a preparation method thereof, which stabilizes the LiBH4 phase by lithium halide doping, and further densifies the intergranular gap by B2O3 compounding to reduce the grain boundary impedance, thereby improving the ability of lithium borohydride-based solid electrolyte to inhibit lithium dendrites, so as to ensure its stable operation under high pressure. The electrolyte conductivity of this modified lithium borohydride electrolyte can reach 1.45×10 -4 S cm -1, has high ionic conductivity, low electronic conductivity and wide electrochemical window in all-solid-state lithium-ion battery applications, and has good stability and compatibility with lithium metal negative electrodes. Compared with traditional liquid batteries, the all-solid-state lithium-ion battery assembled with the modified borohydride electrolyte proposed in the present invention has the advantages of high cycle stability, high energy density, high safety, etc.; and the preparation process of the present invention is simple, the equipment requirements are not high, the cost is low, and the economic benefits are high, and it can be applied to the large-scale production of high specific energy lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The X-ray diffraction pattern of the halide-doped and oxide-composite-modified lithium borohydride-based electrolyte obtained in Examples 1-3 of the present invention; Figure 2 is a scanning electron microscope image of boron oxide in an embodiment of the present invention; Figure 3 A high-resolution transmission electron micrograph of the halide-doped and oxide-composite-modified lithium borohydride-based electrolyte obtained in an embodiment of the present invention; Figure 4 Schematic diagram of the curve of the conductivity of xLiBH4-LiX, LiBH4, (xLiBH4-LiX)y-B2O3 electrolytes changing with temperature in the embodiments of the present invention; Figure 5 This is a comparison diagram of activation energies of the halide-doped and oxide-composite-modified lithium borohydride-based electrolytes obtained in the embodiments of the present invention; Figure 6 Schematic diagram of the electrochemical stability test results of the electrolyte material obtained in the embodiment of the present invention; Figure 7 : is the DC polarization curve of the halide-doped and oxide-composite lithium borohydride-based electrolyte obtained in the embodiment of the present invention at 100°C; Figure 8 This is a long cycle performance test diagram of a lithium symmetric battery assembled with a halide-doped and oxide-composite lithium borohydride-based electrolyte in an embodiment of the present invention; Fig. 9 The charge and discharge curves and coulombic efficiency diagram of the lithium-sulfur full battery assembled with halide-doped and oxide-composite lithium borohydride-based electrolyte at 0.1C in the embodiment of the present invention. DETAILED DESCRIPTION
[0011] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments: Example 1
[0012] A preparation method of a halide-doped and oxide-composite synergistically modified lithium borohydride solid electrolyte comprises the following steps: in an air-tight state (H2O<0.01 ppm, O2<0.01 ppm), using a mortar to uniformly mix LiBH4 and LiCl in a molar ratio of 5:1 and transfer the mixture to a stainless steel ball mill, using a planetary ball mill for high-energy ball milling, sealing the ball mill in an inert gas atmosphere, and rotating the ball mill at a speed of 600 rpm. rpm, and the ball milling time is 3 hours, wherein the ball-to-material ratio is 120:1; after ball milling, the product is transferred to a stainless steel reaction tube under an inert gas atmosphere, heated to 110°C at a heating rate of 5°C / min, kept warm for 3 hours, and cooled to room temperature to obtain a lithium chloride-doped lithium borohydride-based xLiBH4-LiCl (x=5) electrolyte; the above product is then mixed with boron oxide in a molar ratio of 20:1 and transferred to a stainless steel ball mill jar, and high-energy ball milling is performed using a planetary ball mill. The ball mill jar is sealed under an inert gas atmosphere, the ball-to-material ratio is 100:1, the ball milling revolution speed is 400 rpm, and the ball milling time is 2 hours. The obtained product is a lithium chloride-doped and boron oxide-composite lithium borohydride-based (xLiBH4-LiCl)y-B2O3 (y=20) electrolyte. Example 2
[0013] A preparation method of a halide-doped and oxide-composite synergistically modified lithium borohydride solid electrolyte comprises the following steps: in an air-tight state (H2O<0.01 ppm, O2<0.01 ppm), using a mortar to uniformly mix LiBH4 and LiBr in a molar ratio of 5:1 and transfer the mixture to a stainless steel ball mill, using a planetary ball mill for high-energy ball milling, sealing the ball mill in an inert gas atmosphere, and rotating the ball mill at a speed of 600 rpm. rpm, and the ball milling time is 3 hours, wherein the ball-to-material ratio is 120:1; after ball milling, the product is transferred to a stainless steel reaction tube under an inert gas atmosphere, heated to 110°C at a heating rate of 5°C / min, kept warm for 3 hours, and cooled to room temperature to obtain a lithium bromide-doped lithium borohydride-based xLiBH4-LiBr (x=5) electrolyte; the above product is then mixed with boron oxide in a molar ratio of 18:1 and transferred to a stainless steel ball mill jar, and high-energy ball milling is performed using a planetary ball mill. The ball mill jar is sealed under an inert gas atmosphere, the ball-to-material ratio is 100:1, the ball milling revolution speed is 400 rpm, and the ball milling time is 2 hours. The obtained product is a lithium bromide-doped and boron oxide-composite lithium borohydride-based (xLiBH4-LiBr)y-B2O3 (y=18) electrolyte. Example 3
[0014] A preparation method of a halide-doped and oxide-composite synergistically modified lithium borohydride solid electrolyte comprises the following steps: in an air-tight state (H2O<0.01 ppm, O2<0.01 ppm), using a mortar to uniformly mix LiBH4 and LiI in a molar ratio of 5:1 and transfer the mixture to a stainless steel ball mill, using a planetary ball mill for high-energy ball milling, sealing the ball mill in an inert gas atmosphere, and rotating the ball mill at a speed of 600 rpm, and the ball milling time is 3 hours, wherein the ball-to-material ratio is 120:1; after ball milling, the product is transferred to a stainless steel reaction tube under an inert gas atmosphere, heated to 110°C at a heating rate of 5°C / min, kept warm for 3 hours, and cooled to room temperature to obtain a lithium iodide-doped lithium borohydride-based xLiBH4-LiI (x=5) electrolyte; the above product is then mixed with boron oxide in a molar ratio of 16:1 and transferred to a stainless steel ball mill jar, and high-energy ball milling is performed using a planetary ball mill. The ball mill jar is sealed under an inert gas atmosphere, the ball-to-material ratio is 100:1, the ball milling revolution speed is 400 rpm, and the ball milling time is 2 hours. The obtained product is a lithium iodide-doped and boron oxide-composite lithium borohydride-based (xLiBH4-LiI)y-B2O3 (y=16) electrolyte. Example 4
[0015] A preparation method of a halide-doped and oxide-composite synergistically modified lithium borohydride solid electrolyte comprises the following steps: in an air-tight state (H2O<0.01 ppm, O2<0.01 ppm), using a mortar to uniformly mix LiBH4 and LiCl in a molar ratio of 5:1 and transfer the mixture to a stainless steel ball mill, using a planetary ball mill for high-energy ball milling, sealing the ball mill in an inert gas atmosphere, and rotating the ball mill at a speed of 600 rpm. rpm, and the ball milling time is 3 hours, wherein the ball-to-material ratio is 120:1; after ball milling, the product is transferred to a stainless steel reaction tube under an inert gas atmosphere, heated to 110°C at a heating rate of 5°C / min, kept warm for 3 hours, and cooled to room temperature to obtain a lithium chloride-doped lithium borohydride-based xLiBH4-LiCl (x=5) electrolyte; the above product is then mixed with boron oxide in a molar ratio of 14:1 and transferred to a stainless steel ball mill jar, and high-energy ball milling is performed using a planetary ball mill. The ball mill jar is sealed under an inert gas atmosphere, the ball-to-material ratio is 100:1, the ball milling revolution speed is 400 rpm, and the ball milling time is 2 hours. The obtained product is a lithium chloride-doped and boron oxide-composite lithium borohydride-based (xLiBH4-LiCl)y-B2O3 (y=14) electrolyte. Example 5
[0016] A preparation method of a halide-doped and oxide-composite synergistically modified lithium borohydride solid electrolyte comprises the following steps: in an air-tight state (H2O<0.01 ppm, O2<0.01 ppm), using a mortar to uniformly mix LiBH4 and LiBr in a molar ratio of 5:1 and transfer the mixture to a stainless steel ball mill, using a planetary ball mill for high-energy ball milling, sealing the ball mill in an inert gas atmosphere, the ball milling orbital speed is 600 rpm, the ball milling time is 3 hours, wherein the ball-to-material ratio is 120:1; after ball milling, transferring the product to a stainless steel reaction tube in an inert gas atmosphere, heating the mixture to 110 °C at a heating rate of 5 °C / min, and heating the mixture to 110 °C at a heating rate of 5 °C / min. ℃, keep warm for 3 hours, cool to room temperature to obtain halide-doped lithium borohydride-based xLiBH4-LiBr (x=5) electrolyte; then mix the above product with boron oxide in a molar ratio of 12:1 and transfer it to a stainless steel ball mill, use a planetary ball mill for high-energy ball milling, seal the ball mill in an inert gas atmosphere, the ball-to-material ratio is 100:1, the ball mill revolution speed is 400 rpm, the ball milling time is 2 hours, and the resulting product is lithium bromide-doped and boron oxide-composite lithium borohydride-based (xLiBH4-LiBr)y-B2O3 (y=12) electrolyte.
[0017] Figure 1 The X-ray diffraction patterns of the composite lithium borohydride-based electrolytes obtained in Examples 1 to 3 are shown, and it can be found that the doping of LiX and the compounding of B2O3 do not change the phase structure of LiBH4; Figure 2 Shown is a scanning electron microscope image showing that the unmilled boron oxide is in the form of irregular particles; Figure 3 The high-resolution transmission electron micrograph shown shows that the presence of the lithium borohydride phase can be clearly seen from the lattice fringes; Figure 4 The conductivity versus temperature graph shown shows that the lithium halide and boron oxide work together to increase the ionic conductivity of lithium borohydride; Figure 5 The comparison diagram of the activation energy of the electrolytes obtained in Examples 3 to 5 shows that the activation energy of lithium ion migration becomes lower under the combined action of lithium halide and boron oxide; Figure 6 The electrochemical stability test results of the electrolyte material obtained in Example 3 are shown, indicating that halide doping and oxide compounding significantly broaden the potential window of the hydride electrolyte; Figure 7 The DC polarization curve of the electrolyte obtained in Example 3 at 100°C is shown. Its electronic conductivity is as low as 10 -10 S cm -1 ; Figure 8The long cycle performance test diagram of the lithium-lithium symmetrical battery assembled with the electrolyte obtained in Example 3 shows that at 0.1C (1C=1675 mA hg -1 ) cycled 100 times. It can be seen from the figure that it is compatible with lithium metal and maintains long-term stable cycling; Fig. 9 The charge and discharge curves and coulomb efficiency diagram of the lithium-sulfur full battery assembled with the electrolyte obtained in Example 3 at 0.1C, wherein the positive electrode active material is sulfide polyacrylonitrile and the negative electrode is metallic lithium. It can be seen that the battery assembled with the electrolyte after halide doping and oxide composite has good cycle stability.
[0018] The above-described embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are all within the protection scope of the present invention.
Claims
1. A modified lithium borohydride solid electrolyte, characterized in that: The electrolyte is a (xLiBH4-LiX)y-B2O3 solid electrolyte modified by doping and composite synergistically, wherein x=1-5 and y=10-20; the LiX is doped with LiBH4 to form a solid solution, and then the grain gap is densified through B2O3 composite.
2. A method for preparing a modified lithium borohydride solid electrolyte, characterized in that: The following steps are involved: (1) mixing LiBH4 and LiX under an inert gas condition to obtain a mixture; (2) High-energy ball milling of the mixture of LiBH4 and LiX under an inert gas atmosphere; (3) placing the ball-milled product in an inert gas atmosphere and heating it to a predetermined temperature for heat preservation to obtain a xLiBH4-LiX solid solution; (4) mixing the xLiBH4-LiX solid solution with B2O3 in an air-tight condition; (5) Under an inert gas atmosphere, the mixture of xLiBH4-LiX and B2O3 was subjected to high-energy ball milling to obtain the doped and composite synergistically modified (xLiBH4-LiX)y-B2O3 solid electrolyte.
3. The method for preparing the modified lithium borohydride solid electrolyte according to claim 2, characterized in that: The LiX is one or more of LiCl, LiBr and LiI.
4. The method for preparing the modified lithium borohydride solid electrolyte according to claim 2, characterized in that: The inert gas atmosphere is argon, helium or nitrogen.
5. The method for preparing the modified lithium borohydride solid electrolyte according to claim 2, characterized in that: The isolation air conditions are H2O<0.01 ppm, O2<0.01 ppm.
6. The method for preparing the modified lithium borohydride solid electrolyte according to claim 2, characterized in that: The ball-to-material ratio of the high-energy ball mill is (70-140):1, the ball mill revolution speed is 350-600 rpm, and the ball mill time is 1-5 hours.
7. The method for preparing the modified lithium borohydride solid electrolyte according to claim 2 or 6, characterized in that: The high energy ball mill is a planetary ball mill.
8. The method for preparing the modified lithium borohydride solid electrolyte according to claim 2 or 6, characterized in that: The ball-milled LiBH4 and LiX are heated in an inert gas atmosphere at a heating rate of 5°C / min to 110~150°C and kept for 1~5 h to allow LiBH4 and LiX to react fully, and then cooled to room temperature to obtain a LiX-doped LiBH4 xLiBH4-LiX solid solution.
9. The method for preparing the modified lithium borohydride solid electrolyte according to claim 8, characterized in that: The x in the xLiBH4-LiX is 1-5.
10. The method for preparing the modified lithium borohydride solid electrolyte according to claim 2, characterized in that: The y in the (xLiBH4-LiX)y-B2O3 is 10~20.
Citation Information
Patent Citations
Solid electrolyte, method for producing the same, and secondary battery comprising solid electrolyte
CN102017269A
Oxide solid electrolyte and preparation method and application thereof
CN115799619A
Cited By
Hydride solid electrolyte and preparation method and application thereof
CN121528994A
Lithium borohydride-ammonium halide composite solid electrolyte as well as preparation method and application thereof
CN122177957A
A lithium borohydride-ammonium halide composite solid electrolyte, its preparation method and application
CN122177957B